Peran Media Sosial Instagram BPBD Sumatera Barat dalam Penyebaran Informasi Bencana Alam di Sumatera Barat - Hafizul Hamda; Yusalina Yusalina (Lembaga Pengembangan Kinerja Dosen, 2026)
West Sumatra is one of the Indonesian regions with high exposure to natural hazards, making fast, accurate, and accessible disaster information essential. This study aims to analyze the role of the Instagram account of the West Sumatra Regional Disaster Management Agency (BPBD) in disseminating disaster information, examining both institutional management practices and public interpretation of the messages. The study used a descriptive qualitative approach. Data were collected through semi-structured interviews with ten external informants and six internal BPBD informants, supported by observation and documentation of Instagram-based disaster communication. The data were analyzed through reduction, data display, and conclusion drawing. The findings show that Instagram functions as a channel for early warning, emergency updates, disaster education, documentation, and public interaction. Internal informants described content production through field documentation, editing, 5W+1H-based narration, verification, and coordination with related agencies. Public informants perceived BPBD information as clear, credible, and useful for daily preparedness, although they expected faster updates, simpler visuals, and more interactive content. The study implies that disaster communication through Instagram needs to strengthen verification procedures, real-time updates, human resources, and two-way engagement.